Development of in-place permeability criteria for HMA pavement in Wisconsin - Owusu-Ababio, Samuel; Schmitt, Robert; Cooley, Allen L.; Crovetti, James A. (Wisconsin Highway Research Program, 2007)
The purpose of this study is the development of permeability and density acceptance criteria for hot mix asphalt (HMA) pavements in Wisconsin. The work detailed in this report is Phase I of II. Databases from the Pavement Management Unit of the Wisconsin Department of Transportation (WisDOT) were obtained for design, new construction reports, traffic, and performance data to assemble a profile of higher and lower performing pavements within a similar geographic region and truck traffic. Specific field tests on each project included water permeability with the NCAT device, air permeability with the ROMUS device, nuclear density, cores, and pavement distress surveys. Only fine-graded mixtures were tested. In-service pavements were nearly impermeable, where water permeability rates ranged from 0 to 5 x 10 to the -5 power cm/sec, and air permeability rates were a factor of 10 greater than water permeability. Water permeability between wheel paths were generally higher than in the wheel paths. In-service pavement density ranged from 92% to 99%. Air permeability trended downward with an increase in density, while water permeability had no discernible trend. A methodology for developing design criteria for permeability and density based on preliminary findings was presented. Defining specific criteria requires establishing a target Pavement Distress Index (PDI) to yield an expected design permeability, which in turn specifies as-built density at construction. Similarly, the target PDI/year determines the as-built density, to achieve the target value. Based on limited data, it was not possible to establish definitive criteria for permeability and density. A work plan was proposed for Phase II of the study to produce performance models that will establish specific criteria. Phase II will require a long-term study of about 5 years. As-built construction data will be collected on projects throughout the state having varying density requirements, then performance data will be collected and there will be monitoring every other year until the pavement reaches 8 years of age.
80 p.
Keywords: Hot mix paving mixtures; Density; Pavement performance; Asphalt pavements; Acceptance tests; Pavement distress; Permeability; Field tests; Wisconsin